Long-term disease control in dedifferentiated liposarcoma: a case report on trabectedin priming followed by PD-1 inhibition - Waldschmidt, Johannes M.; Haug, Lukas; Riedhammer, Christine; Deinzer, Christoph K. W.; Zimmermann, Marcus; Heidemeier, Anke; Raab, Peter; Rudert, Maximilian; Hendricks, Anne; Lock, Johan F.; Buck, Viktoria; Rosenwald, Andreas; et al. (Frontiers in Oncology, 2025)
BackgroundDedifferentiated liposarcoma (DDLPS) is a rare mesenchymal cancer originating from the adipose tissue, with poor survival rates for most patients, highlighting the critical need for novel treatment options.Case descriptionThis report examines the efficacy and safety of sequential pre-treatment with the marine-derived alkaloid trabectedin followed by checkpoint inhibition using the anti-PD-1 antibody nivolumab in a 63-year-old male patient with unresectable retroperitoneal DDLPS. Treatment was initiated at the time of the seventh relapse as part of the NitraSarc phase 2 multicenter trial for inoperable soft tissue sarcoma conducted by the German Interdisciplinary Sarcoma Group (GISG-15, NCT03590210). The patient demonstrated an immediate tumor response, and in combination with minor surgery, achieved R0 resection status, which was subsequently maintained without the need for further therapy for the past 52 months. Correlative molecular analyses revealed a sustained DNA damage repair machinery and downregulation of PD-1 protein expression in post-treatment tumor samples.ConclusionThis report provides exemplary insight on the feasibility and efficacy of sequential pre-treatment with trabectedin as a priming strategy for PD-1 inhibition in advanced DDLPS. Full trial results from NitraSarc are pending for publication.